Description of Neodolichodorus hainanensis n. sp. (Nematoda: Dolichodoridae) from rhizosphere soil of golf turf in China - Xu, Chun-Ling; Xie, Hui; Li, Yu (Zootaxa, 2012)
Neodolichodorus hainanensis n.sp. is described from China, extracted from soil around turf in a golf course. N. hainanensisn.sp. is characterized by having a conspicuous offset cephalic region with 6–7 striae, divided into 4 lobes; stylet a little shorter(82–100 µm) than most species in this genus; lateral field with four incisures, areolated, with outer lateral field regularlycrossed by every second external stria at most of body length, and inner lateral field partly or wholly irregularly crossed byextending external striae; subconoid tail with rounded terminus; gubernaculum and spicule slightly protruding from cloaca, middle bursa lobe small with a bifid extremity in ventral view.